Экономическая эффективность повышения ресурса режущих элементов землеройно-транспортных машин ионно-плазменным напылением - Калабухин, Ю. Е.; Венцель, Е. С.; Щукин, А. В. (НТУ "ХПИ", 2014)
Приведены методика и результаты расчета экономической эффективности повышения ресурса рабочих органов путем нанесения ионно-плазменного покрытия TiN-Cr2N методом конденсации ионной бомбардировки на поверхность режущих элементов землеройно- транспортных машин (ЗТМ), в частности, ножей автогрейдера.

The paper presents the method and the results of calculation of economic effectiveness of increase of operational life of work tools by ionic plasma deposition of TiN-Cr2N using the method of condensation of ion bombardment of the surface of cutters of earth-moving machines (EMM), in particular, motor grader slice tools.
Еconomic efficiency of increase of operational life of cutter elements of earth-moving machines by means of ionic plasma deposition
Keywords: автогрейдер; рабочий орган; покрытие; затраты; себестоимость; годовой доход; экономический эффект; motor grader; work tool; life; cutter; deposition; costs; self-costs; annual income; economic effect